2011
DOI: 10.1016/j.jvs.2010.10.122
|View full text |Cite
|
Sign up to set email alerts
|

Haptoglobin phenotypes and plasma haptoglobin levels in patients with abdominal aortic aneurysm

Abstract: Our findings suggest that plasma Hp concentrations are elevated in patients with AAA, particularly those with the Hp 2-2 phenotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 32 publications
2
25
0
Order By: Relevance
“…This may be because the purification process involved in the Hp immunoassay is challenging [17,18]. Of note, we have previously reported that plasma Hp concentrations are elevated in patients with abdominal aortic aneurysm (perhaps due to inflammation in the destructive elastic laminae of arteries) [19]. The aim of this study was to investigate plasma Hp concentrations and Hp phenotype in a cohort of Chinese patients with coronary artery disease (CAD).…”
Section: Introductionmentioning
confidence: 99%
“…This may be because the purification process involved in the Hp immunoassay is challenging [17,18]. Of note, we have previously reported that plasma Hp concentrations are elevated in patients with abdominal aortic aneurysm (perhaps due to inflammation in the destructive elastic laminae of arteries) [19]. The aim of this study was to investigate plasma Hp concentrations and Hp phenotype in a cohort of Chinese patients with coronary artery disease (CAD).…”
Section: Introductionmentioning
confidence: 99%
“…For the remaining 18 patients, the mean haptoglobin on day 0 was 274 ± 142 mg/dl (median 283, range 59-551). There was no correlation between patient age and baseline haptoglobin levels (data not shown, R=0.004) [15].…”
Section: Patientsmentioning
confidence: 87%
“…The normal range during the study period was 22-239 mg/dl. Haptoglobin phenotyping (Hp1, Hp2) was not performed [2,15].…”
Section: Haptoglobin Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, Pan et al [38] demonstrated that plasma Hp concentration was elevated in patients with AAA, particularly those with the Hp 2-2 phenotype. They suggested that if the results of this study were confirmed and extended by a further larger scale study, Hp concentration among with Hp2-2 phenotype might be potential biomarkers of AAA development and could be used clinically in association with other biomarkers [38]. Concerning proteins belonging to lipid metabolic process, we found apolipoproteins.…”
Section: Go:0006955 Immune Responsementioning
confidence: 99%